ENGINEERING INNOVATION FOR RURAL WASTE MANAGEMENT: DEVELOPMENT OF AN ORGANIC WASTE CHOPPER MACHINE IN JEMBER REGENCY - Mahros Darsin; Hari Arbiantara Basuki; Danang Yudistito; Robertoes Koekoeh Koentjoro Wibowo; Fikril Hilmi; Dwi Djumhariyanto; Muhammad Maulana Andi Surya; Hafidz Ahmad Abdillah; Muhamad Zaky Rizqullah Nurrosidi; Deni Yudas Priawan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Waste management remains a critical challenge in rural and semi-urban communities in Indonesia, where limited infrastructure and low public awareness often lead to environmental degradation. Jelbuk Village in Jember Regency produces approximately 1,200 kg of household waste per day, most of which is disposed of in rivers or vacant land. This condition has resulted in pollution, health risks, and flooding, while the economic potential of waste recycling remains untapped. To address these issues, the Universitas Jember community service team implemented an integrated waste management program that combines technical innovation with community empowerment. The technical approach involved designing and fabricating a portable organic waste chopper machine with a capacity of 120 kg/hour, enabling the production of compost from organic waste. In parallel, inorganic waste such as plastics and metals was separated for recycling. The non-technical approach included training, awareness campaigns, and mentoring in simple bookkeeping to strengthen community capacity for sustainable waste management. The program successfully reduced waste accumulation, improved sanitation, and created new economic opportunities through compost production and the sale of recyclable materials. Furthermore, the involvement of students in design and implementation enhanced academic outcomes and knowledge transfer. This initiative demonstrates that integrated technical and social approaches can effectively transform waste problems into community-based solutions with long-term sustainability.